Longer School Schedules, Childcare and the Quality of Mothers' Employment: Evidence from School Reform in Chile - Matias Berthelon; Diana Kruger; Catalina Lauer; Luca Tiberti; Carlos Zamora (Global Labor Organization (GLO), 2020)
Ample empirical evidence has found that access to childcare for preschool children increases mothers' labor force participation and employment. In this paper, we investigate whether increased childcare for primary school children improves the quality of jobs mothers find by estimating the causal effect of a school schedule reform in Chile. Combining plausibly exogenous temporal and spatial variations in school schedules with a panel of individual mothers' employment between 2002 and 2015, we estimated a fixed-effects model that controlled for unobserved heterogeneity. We found a positive effect of access to full-day schools on several measures of 'the quality of mothers' jobs, which were correlated to working full-time. We also found small, positive effects on quality of fathers' jobs. Our evidence suggests that the mechanism driving the effect was the effect of the reform's implicit subsidy to the cost of childcare on the opportunity cost of mothers' time. We also found that less educated mothers benefited most from the reform. Thus, childcare can increase household welfare by improving parents' jobs and can play a role in reducing inequality.
Keywords: H41; H52; I25; I28; J13; J16; J18; J22; O15; 330; Employment quality; job quality; women's labor force participation; women's labor supply; full-day schooling; childcare; education reform; Chile